Roman Polanski - Morrison, James, 1960- (Urbana : University of Illinois Press, 2007)
James Morrison's Roman Polanski offers one of the most comprehensive and critically engaged treatments ever written on Polanski's work. Tracing the filmmaker's remarkably diverse career from its beginnings to the present, the book provides commentary on all his major films in their historical, cultural, social, and artistic contexts. By locating Polanski's work within the genres of comedy and melodrama, Morrison argues that this eclectic and controversial director is not merely obsessed with the theme of repression, but that his true interest is in the concrete--what is out in the open--and in why it is so rarely seen. The range of Polanski's filmmaking challenges traditional divisions between high and low culture, as exhibited in two of his recent and very different films: The Ninth Gate, a brash pastiche of the horror genre, and The Pianist, an Academy Award-winning film about the Holocaust. In dubbing Polanski a relentless critic of modernity, Morrison concludes that his career is representative of the fissures, victories, and rehabilitations of the last fifty years of international cinema.
Captive Minds: Polanski and Modernity -- Comedy, Melodrama, and Genrification in Polanski's Films -- Cul-de-Sac and the 1960s Art Cinema -- Polanski in the New Hollywood -- Polanski and Art Film's Second Wave -- Rendering Classics: Macbeth and Tess -- Discovering the Figural in Polanski's Films -- Interviews with Roman Polanski.
Includes bibliographical references (pages 179-184) and index.
Includes filmography: pages 169-177.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Polanski, Roman -- Criticism and interpretation; Polanski, Roman; Polański, Roman -- 1933-; Bibel; Polanski, Roman; Motion pictures -- Poland -- History; Cinéma -- Pologne -- Histoire; PERFORMING ARTS / General; Motion pictures; Poland; Film; Regissörer.; Criticism, interpretation, etc; History